Higher Negative Self-Reference Level in Patients With Personality Disorders and Suicide Attempt(s) History During Biological Treatment for Major Depressive Disorder: Clinical Implications - Bulteau, Samuel; Péré, Morgane; Blanchin, Myriam; Poulet, Emmanuel; Brunelin, Jérôme; Sauvaget, Anne; Sébille, Véronique (Frontiers in Psychology, 2021)
OBJECTIVE The aim of the study was to identify clinical variables associated with changes in specific domains of self-reported depression during treatment by antidepressant and/or repetitive Transcranial Magnetic Stimulation (rTMS). METHODS Data from a trial involving 170 patients with Major Depressive Disorder (MDD) receiving either venlafaxine, rTMS or both were re-analyzed. Depressive symptoms were assessed each week during the 2 to 6 weeks of treatment with the 13-item Beck Depression Inventory (BDI13) and the 21-items Hamilton Depression Rating Scale (HDRS21) Associations between depression changes on BDI13 domains (Sad Mood, Negative Self-Reference, and Performance Impairment), the total score of HDRS21, treatment arm, time, and clinical variables were tested in a mixed linear model. RESULTS A significant decrease of self-reported depressive symptoms was observed over time as assessed with the HDRS21 scores (-2.6 points/week). Depressive symptomatology on Negative Self-Reference domain of the BDI13 was higher for patients with personality disorders (+2.12 points), past history of suicide attempts (+1.70 points) and female sex (+1.07 points). CONCLUSIONS Cognitive intervention targeting specifically negative self-referencing process could be considered during pharmacological and rTMS treatment for patients with personality disorders and past history of suicide attempts.